Cercyon (Cercyon) aptus Sharp 1873 ... - Sazhnev, A. S.; Prokin, A. A.; Sergeev, M. E. (Zenodo, 2021)
Cercyon (Cercyon) aptus Sharp, 1873 MATERIAL EXAMINED. 4: 15.VII.2017, 3 exs. DISTRIBUTION. China (Hebei), Russian Far East (Kuril Islands, Primorsky Krai, Sakhalin), Japan [Shatrovskij, 1992; Hebauer, 1995; Ryndevich, 2003; Ôhara, Jia, 2006; Prokin, 2009; Fikáček et al., 2015]. ... : Published as part of Sazhnev, A. S., Prokin, A. A. & Sergeev, M. E., 2021, New data on water beetles (Coleoptera: Gyrinidae, Haliplidae, Noteridae, Dytiscidae, Hydrophilidae, Elmidae) of Primorsky Krai (Russia), pp. 264-274 in Russian Entomological Journal 30 (3) on page 268, DOI: 10.15298/rusentj.30.3.03, http://zenodo.org/record/13178748 ...